Aktivitas Antibakteri Gel Hand Sanitizer Minyak Biji Pala (Myristica fragrans Houtt.) dengan Variasi Gelling Agent - RACHMAWATI DWI AGUSTIN; YUNIASIH MULYANI JUBELIENE TAIHUTTU (Hang Tuah Medical Journal, 2025)
Hand hygiene is important because hands are one of the intermediary pathways for the entry of microbes into the body. Efforts to maintain cleanliness by diligently washing hands and using a practical way of using hand sanitizer. The alcohol content in hand sanitizers can have a long-term impact on skin health, for that alternative alcohol substitutes can use natural ingredients as the basic ingredients of antiseptic hand sanitizers. Nutmeg seed oil contains active compounds as antibacterial ingredients. This study aims to determine the correct formulation of nutmeg oil hand sanitizer gel preparation and test its effectiveness in inhibiting the growth of pathogenic bacteria, namely Escherichia coli and Pseudomonas aeruginosa. Gel preparations were made with variations of the gelling agent Carbopol and CMC-Na. The stability test of the physical properties of the gel preparation includes organoleptic test, homogeneity test, and pH test. Antibacterial activity test by disc diffusion method. The results showed that the gel preparation had a characteristic nutmeg odor, with a clear color for the CMC-Na base and white for the Carbopol base. The pH values obtained for all preparations ranged from 5.7-6.2. The results of the antibacterial activity test showed that the nutmeg oil hand sanitizer gel based on CMC-Na and Carbopol had the ability to inhibit Escherichia coli and Pseudomonas aeruginosa bacteria quite well. The conclusion of this study is that the formulation of CMC-Na-based nutmeg seed oil gel formulation is considered to be the optimal formulation in inhibiting the growth of pathogenic bacteria and has a consistent physical form.